Accelerating The Mission Of Education: Testing The Power Of Transformational Leadership And Group Cohesiveness In The Organization - M. Saiful Mujab; Munirul Abidin (Studia Manageria, 2025)
Achieving the mission of educational institutions is a crucial factor in the progress of education in Indonesia. Researchers often encounter obstacles in mission achievement due to leadership deficiencies, poor human resource quality, and insufficient support from surrounding groups. Therefore, this research aims to determine the influence of transformational leadership and human resource quality on mission achievement, moderated by group cohesiveness. This study employs a quantitative method, with data collected via Google Form questionnaires, which were distributed through WhatsApp and analyzed using SmartPLS 4. The results indicate that transformational leadership and group cohesiveness have a significant effect on the effectiveness of mission achievement in educational institutions, whereas other variables showed no significant effect. The implications of this research suggest that to enhance mission achievement effectiveness, educational institutions must prioritize the development of transformational leadership character and build a solid and cohesive work climate. This implies that institutional success depends more on the leader's vision and team cohesion than merely on staff qualifications.